EVALUATION IN VITRO OF THE LEUKOCYTE RESPONSE OF ALPACAS (VICUGNA PACOS)IN PRESENCE OF CLOSTRIDIAL ANTIGENS - Tambillo G., Luis (2013)
The aim of this study was to evaluate the expression of proinflammatory cytokines of alpaca circulating leukocytes when confronting total extract of Clostridum perfringens (structural components and toxins). Whole blood was collected from the jugular vein of 5 female and 5 male adult alpacas. The leukocytes were separated using ammonium chloride to lyse erythrocytes followed by centrifugation and then cultured at a concentration of 500 000 cells/ml of MEM (Minimal Essential Medium) in culture plates of 12 wells. Simultaneously were challenged with total extract of C. perfringens grown in thioglycolate broth at concentrations of 400, 80, 16, 0.8 and 0.2 μg/ml and then quantifying by RT-PCR the expression of cytokines TNF∝, IL-1∝, IL-6 and IL-1ß at 1, 12 and 24 h of exposure. The results showed that low doses of clostridial extracts (0.2 to 0.8 mg/ml) are capable of inducing expression of TNF∝, IL-1∝ and IL-1ß at 1, 12 and 24 h of incubation, whereas higher doses do not exceed the expression of cytokines in unstimulated (control) leukocytes. There was no significant production of IL-6 up to 24 h after exposure to whole extract of C. perfringens. These results indicate that C. perfringens and its toxins at low doses induce activation of circulatory leukocyte in alpacas producing proinflammatory cytokine secretion.